Enhancing Manufacturing Readiness Level for New Product Introduction A Case Study Approach - Salonen, Matti (My University, 2026)
A comprehensive literature review was conducted to examine the evolution of Manufacturing Readiness Levels (MRLs), beginning from their origins in the U.S. Department of Defense and extending to their relationship with Technology Readiness Levels (TRLs) and Design Readiness Levels (DRLs). The review also identified the key factors influencing manufacturing readiness, including leadership commitment, workforce competence, technology maturity, process capability, supply chain stability, quality management, and regulatory compliance. Together, these factors form the foundation of effective readiness assessment and highlight the complexity of evaluating manufacturing maturity in New Product Introduction (NPI) projects. The empirical part of the study was carried out as a case study in a manufacturing company operating in a complex industrial environment. A mixed-methods approach was applied, combining qualitative and quantitative elements. Qualitative data were collected through semi-structured interviews with company experts representing design, technology, and manufacturing functions. This was followed by workshops and simulation exercises used to validate and refine the findings in a practical organizational setting. Based on the combined findings, a seven-level MRL framework was developed by merging and refining the traditional ten-level DoD MRL model to better fit the operational context and project practices of the case company. The proposed framework was designed to align with the company’s internal R&D gate process and to reflect the key phases of prototype, pilot, and ramp-up production. A simulation of the scale using a recent product introduction case demonstrated that the framework was generally clear, usable, and well aligned with existing processes. At the same time, the simulation also indicated that further refinement is needed, particularly in relation to documentation practices and the use of data to support readiness decisions more consistently. The results indicate that the customized MRL scale provides a more structured, measurable, and collaborative method for assessing manufacturing maturity than the company’s previous approach. The framework improves the visibility of manufacturing readiness, supports earlier identification of risks and capability gaps, and creates a shared language for communication across stakeholders. In addition, it offers practical value for managerial decision-making by strengthening process transparency, improving coordination between functions, and supporting continuous improvement throughout the NPI process. The thesis concludes that the proposed MRL scale is suitable for early implementation in the case company, but that broader adoption should take place gradually and iteratively in order to ensure data reliability, organizational acceptance, and effective integration into existing project governance. Overall, the study contributes to the development of manufacturing readiness assessment practices by demonstrating how a generic readiness framework can be tailored to a specific industrial context. In doing so, it supports the case company’s capability to carry out more efficient, predictable, and high-quality new product introductions.

Kattava kirjallisuuskatsaus toteutettiin valmistusvalmiustaso (Manufacturing Readiness Level, MRL) -mallin kehityksen tarkastelemiseksi sen alkuperästä Yhdysvaltain puolustusministeriössä aina sen suhteeseen teknologian valmiustaso (Technology Readiness Level, TRL) - ja suunnittelun valmiustaso (Design Readiness Level, DRL) -mallien kanssa. Kirjallisuuskatsauksessa tunnistettiin myös keskeiset valmistusvalmiuteen vaikuttavat tekijät, kuten johdon sitoutuminen, henkilöstön osaaminen, teknologian kypsyys, prosessikyvykkyys, toimitusketjun vakaus, laadunhallinta sekä sääntelyvaatimusten noudattaminen. Nämä tekijät muodostavat tehokkaan valmistusvalmiuden arvioinnin perustan ja korostavat valmistuskypsyyden arvioinnin monimutkaisuutta uusien tuotteiden käyttöönottohankkeissa. Tutkimuksen empiirinen osa toteutettiin tapaustutkimuksena valmistavan teollisuuden yrityksessä, joka toimii monimutkaisessa teollisessa toimintaympäristössä. Tutkimuksessa sovellettiin monimenetelmällistä lähestymistapaa, jossa yhdistettiin laadullisia ja määrällisiä elementtejä. Laadullinen aineisto kerättiin puolistrukturoitujen haastattelujen avulla yrityksen suunnittelun, teknologian ja valmistuksen asiantuntijoilta, ja sitä täydennettiin työpajoilla sekä simulaatioharjoituksilla. Näiden avulla tuloksia validoitiin ja tarkennettiin organisaation käytännön toimintaympäristössä. Yhdistettyjen tulosten perusteella kehitettiin seitsemäntasoinen MRL-viitekehys, joka muodostettiin muokkaamalla perinteistä Yhdysvaltain puolustusministeriön kymmentasoista MRL-mallia tapausyrityksen toimintaympäristöön ja projektikäytäntöihin paremmin soveltuvaksi. Viitekehys suunniteltiin vastaamaan yrityksen sisäistä tuotekehityksen porttimallia sekä heijastamaan prototyyppi-, pilotti- ja ylösajovaiheiden keskeisiä tuotannollisia vaiheita. Viitekehyksen simulointi äskettäisen tuoteintroduktiotapauksen avulla osoitti, että malli oli pääosin selkeä, käyttökelpoinen ja hyvin linjassa olemassa olevien prosessien kanssa. Samalla havaittiin, että viitekehys vaatii vielä jatkokehitystä erityisesti dokumentointikäytäntöjen sekä valmiuspäätöksiä tukevan tiedon systemaattisemman hyödyntämisen osalta. Tulokset osoittavat, että räätälöity MRL-malli tarjoaa aiempaa jäsennellymmän, mitattavamman ja yhteistyötä paremmin tukevan menetelmän valmistuskypsyyden arviointiin. Se parantaa valmistusvalmiuden näkyvyyttä, tukee riskien ja kyvykkyyspuut teiden aiempaa tunnistamista sekä luo yhteisen kielen sidosryhmien väliselle viestinnälle. Lisäksi se tukee johtamistyötä vahvistamalla prosessien läpinäkyvyyttä, parantamalla toimintojen välistä koordinointia ja edistämällä jatkuvaa kehittämistä uusien tuotteiden käyttöönoton aikana. Tutkielman johtopäätöksenä todetaan, että ehdotettu MRL-malli soveltuu tapausyrityksessä varhaiseen käyttöönottoon, mutta laajemman käyttöönoton tulisi edetä vaiheittain ja iteratiivisesti, jotta tiedon luotettavuus, organisaation hyväksyntä ja tehokas integroituminen olemassa olevaan projektiohjaukseen voidaan varmistaa. Kokonaisuutena tutkimus osoittaa, kuinka yleinen valmiusarvioinnin viitekehys voidaan räätälöidä tiettyyn teolliseen kontekstiin ja siten tukea uusien tuoteintroduktioiden toteuttamista tehokkaammin, ennakoitavammin ja laadukkaammin.
Keywords: manufacturing; production; process management; risk management; factors of production; industrial companies; Industrial Systems Analytics; Master's Programme in Industrial Systems Analytics